Comprehensive genome annotation of Trilocha varians, a new model species of Lepidopteran insects - Jung Lee; Toshiaki Fujimoto; Katsushi Yamaguchi; Shuji Shigenobu; Ken Sahara; Toru Shimada (Scientific Data)
Abstract Trilocha varians is a member of the bombycid moths. Since T. varians has a considerably shorter generation period than the prevailing model species, Bombyx mori, this species would be a novel model insect in Lepidoptera. To facilitate further use of T. varians, we developed genome annotation information on the chromosome-scale assembly of T. varians previously published by our group. 9 RNA-seq datasets and 2 Iso-seq datasets were submitted for transcriptome-based gene prediction. As a result, 16,266 protein-coding genes were predicted on the latest genome assembly, and 98.6% of BUSCO sequences were present in our gene models. ATAC-seq was also conducted to determine chromatin accessibility across the genome. Finally, piRNA-targeted small RNA-seq revealed T. varians genome harbours 517 piRNA clusters (piCs). This information will encourage and facilitate potential users who plan to use this species.